NEW FORMULATED VANISHING SKIN CREAM CONTAINING SRI LANKAN RAW HONEY VS MARKETED CREAMS WITH HONEY: A COMPARATIVE STUDY - R.K.K.N.S. Ranasinghe; L.C.P.T. Lianaarachchie; R.A.D.M. Ranasinghe; T.M.I.U.K. Tennakoon (Current Research in Pharmaceutical Sciences, 2025)
Aims: Cosmetics containing natural ingredients have become more popular nowadays due to their ability to beautify and treatment of skin ailments. Honey is an organic natural substance with various benefits and traditional uses. The objective of this study was to formulate a new vanishing skin cream incorporating Sri Lankan raw honey and to compare it with creams already available in the market.Methods: Three different bee honey concentrations of Sri Lankan origin were incorporated into vanishing cream bases to produce three new cosmetic creams (F1-12.5% w/w, F2-18.75% w/w, F3-25% w/w). They were compared with three different commercially available cosmetic creams (C1-local honey (Honey day cream/Fairness day moisturizer, Ovi, Sri Lanka), C2-foreign honey (Almond milk and honey cream, Body Shop, USA), C3-foreign (Milk and honey gold nourishing hand and body cream, Oriflame, Sweden) for stability, antibacterial activity (agar well diffusion assay), and antioxidant activity (DPPH assay).Results: All cream formulations were stable at room temperature (25℃) and produced inhibitory zones against Escherichia coli and Staphylococcus aureus. DPPH assay revealed that all cream samples have antioxidant activity. The pH of laboratory-made cream formulations containing Sri Lankan raw honey was compatible to be used for topical application. C1 cream showed the highest antioxidant and antibacterial activity compared to all other creams. Antioxidant and antibacterial activities increased with increasing honey concentrations for formulated creams.Conclusions: It is concluded that the laboratory-made new cream formulations containing Sri Lankan raw honey were compatible to be used for topical application compared with the creams already in the market and have future potential as a cosmeceutical.